Evaluasi Kinerja Proyek Peningkatan Jaringan Irigasi Tukad Petanu Berdasarkan Earned Value Analysis - Yuliana, Ni Putu Indah; Ni Kadek Sri Ebtha Yuni (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2021)
The achievements review of Tukad Petanu irrigation network improvement project still uses traditional cost management concept so that the evaluation based on value analysis needs to be done. The purpose of the research’s is to analyze project’s cost and time performance based on earned value analysis. This research uses quantitative descriptive with earned value analysis. Based on analysis, from 1st to 8th month the value of Budgeted Cost Work Performance (BCWP) is above Budgeted Cost Work Schedule (BCWS) and ends at the same point in 9th month so it categorized run faster 6,52% of planned time and ends according to planned time. The Actual Cost Work Performance (ACWP) value is below the BCWP so the actual costs are less than planned costs, which is 21.14% of planned costs. Analysis of cost and time variance based on cumulative have a positive value (+), shows the work is run faster than planned and the costs are smaller than the budget. The cumulative cost and time performance index have an average Cost Performance Index (CPI) of 1.21 and an average Schedule Performance Index (SPI) of 1.02 so the project runs faster than planned time and costs are smaller than planned budget.